Clinical study of a method for the receptor apparatus of the teeth protection at the stages of treatment with non-removable prosthesis designs - Voznyi, O.; Yanishen, I.; Diudina, Iryna; Tomilin, V.; Pohorila, A. (My University, 2020)
This article presents the results of clinical approbation of our proposed method for protecting the receptor apparatus of the teeth through a complex of domestic light-curing adhesive preparations and antihomotoxic drug “Traumeel”, the application of which was substantiated by experimental studies in laboratory animals.
Keywords: receptor apparatus; intact teeth; electroodontometry; mastication; mastication; lightcuring adhesive; antihomotoxic drug